Kontak dengan Alam Sebagai Media Peminimalisir Mengatasi Stres Ringan - Nia Azizunnisa (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This article discusses contact with nature as a medium to minimize mild stress. At a mild level, stress can actually increase the enthusiasm for life in fighting challenges, but if stress increases to a more severe level, it can cause nervous tension, and have an impact on suffering not only physically, but also our soul (mind). The aim of this research is to increase awareness of the importance of contact with nature for mental health. This research uses qualitative research methods, including in the library research category, so in the process of collecting data, the author collects data in the form of information through literature. The results of this research are that contact with nature can minimize mild stress for some people. Activities in nature, such as mountain climbing, camping, or simply walking in the forest, are believed to have therapeutic effects that can improve mental well-being. Nature can have a positive impact on health and well-being. One application can be implemented is through natural schools, nature-based schools which aim to restore essential human values ​​that are one with nature. In nature schools, students are free to interact with the outdoors. Students look cheerful and enjoy learning without any pressure and school does not become a boring prison. This is the most important thing, so that children do not get stressed and bored easily.